Assessment of Russian citizens’ attitude to the processes of public services digitalization - S. P. Kosarin (State University of Management, 2020)
Russia is rapidly increasing the use of digital technologies in all spheres of public life. The speed, with which new technologies appear and are implemented, leads to the fact that people cannot quickly adapt to them. In this regard, in some cases, there may be social tensions, reluctance to use modern advances in digital technologies and other social problems. There is also a overestimation of the importance and impact of the introduced technologies on improving the socio-economic and political life of the country.In this regard, it is of interest to assess the attitude of citizens to the developing digital technologies, and, primarily, to digital services that are introduced in the system of providing state and municipal services and in the sphere of interaction between the state and society. This study is an attempt to make this kind of assessment. The background of the study was the adopting and approving in 2018 the national project “Digital economy of the Russian Federation” and the Federal programs implemented within the framework of this project, as well as the state programs and projects preceding the national project that accompany the formation of the infrastructure of the digital state.The authors conducted a survey of 541 respondents from 49 regions of the Russian Federation to determine and assess the attitude of citizens to the digitalization of public services. During the survey, respondents were asked questions about the use of Federal and regional portals of public services, about awareness of the availability and possibility of using public technologies and services, about the convenience of services and the ability to use them. As a result of the survey, conclusions are drawn about the advantages and disadvantages of using the electronic service of public services, as well as an assessment of the attitude of citizens to the digitalization of public services.